Case Report: Suspected Solitary Osseous Plasmacytoma in a Cat: Use of Magnetic Resonance Imaging to Diagnose and Confirm Resolution of Disease Following Chemotherapy - Moore, Talisha M.; Thomovsky, Stephanie A.; Thompson, Craig A.; Heng, Hock Gan; Bentley, R. Timothy (Frontiers in Veterinary Science, 2021)
A 9-year-old female spayed Domestic Shorthair cat presented for pain, reluctance to jump, and hyporexia of 14 days duration. Neurologic examination was consistent with C6-T2 myelopathy. Magnetic resonance imaging (MRI) revealed a solitary, contrast-enhancing lesion within the T2 vertebral body. Solitary osseous plasmacytoma was diagnosed based on neurologic examination, advanced imaging, and clinicopathologic findings. Melphalan and prednisolone therapy were initiated. Complete resolution of clinical signs and the vertebral lesion were documented at a 2-year follow up examination with neurologic examination and repeat spinal MRI, respectively. Solitary osseous plasmacytoma are rare neoplasms in humans and domestic animals. As such, there is a paucity of published information regarding diagnostic criteria, MRI findings, treatment modalities, progression, and remission of disease in the feline patient. Most data are extrapolated from human medicine. The purpose of this report is to document neurologic exam and MR findings at the time of diagnosis and complete resolution of a solitary osseous vertebral plasmacytoma following melphalan and prednisolone therapy.